2020
DOI: 10.31219/osf.io/v6qsp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving the production and evaluation of structural models using a Delphi process

Abstract: Bayes Nets (BNs) are extremely useful for causal and probabilistic modelling in many real-world applications, often built with information elicited from groups of domain experts. But their potential for reasoning and decision support has been limited by two major factors: the need for significant normative knowledge, and the lack of any validated methods or software supporting collaboration. Consequently, we have developed a web-based structured technique – Bayesian Argumentation via Delphi (BARD) – to enable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Piloting suggested that for our participants and tasks the trade-off is worthwhile. We also have some experimental evidence that even a minimal Delphi-style interaction improves the network structures produced by BARD groups (Bolger et al, 2019). Nevertheless, we do not yet have any direct experimental comparison for BARD groups between traditional Delphi, realtime Delphi, and free interaction.…”
Section: Discussionmentioning
confidence: 96%
“…Piloting suggested that for our participants and tasks the trade-off is worthwhile. We also have some experimental evidence that even a minimal Delphi-style interaction improves the network structures produced by BARD groups (Bolger et al, 2019). Nevertheless, we do not yet have any direct experimental comparison for BARD groups between traditional Delphi, realtime Delphi, and free interaction.…”
Section: Discussionmentioning
confidence: 96%
“…Piloting suggested that for our participants and tasks the tradeoff is worthwhile. We also have some experimental evidence that even a minimal Delphi-style interaction improves the network structures produced by BARD groups (Bolger et al, 2020). Nevertheless, we do not yet have any direct experimental compari-29 A beta-version of BARD is now available that supports decision and utility nodes, and computes expected utilities for decisions.…”
Section: Discussionmentioning
confidence: 99%
“…( 2020 ). This includes a follow‐up experiment we conducted (Bolger et al., 2020 ) to verify whether, and explore how, BARD's Delphi processes contribute, focusing on the core BN‐modeling task of deciding on causal structure. Accuracy of causal structure was measured in a simple, standard way by the edit distance (i.e., the number of arrows that differ) between the structure participants produced and the normatively correct structure.…”
mentioning
confidence: 99%
“…In the Structure Delphi experiment (Bolger et al, 2020), individual participants who had previously used BARD were asked to analyze some of our other reasoning problems they had not previously seen, but only for the critical and most distinctive subtask in BN construction: selecting the right variables and causal structure. All other subtasks in solving our reasoning problems are similar to tasks for which Delphi has already been shown to be effective in prior literature.…”
Section: Experiments Separating Bn Construction From Delphi Collaboramentioning
confidence: 99%
“…Given that our X participants were supposed to achieve better written reports than K by constructing BN models, it is natural to ask how accurate their models turned out to be, and how well-correlated this was to the quality of their written reports. In Bolger et al (2020), our BARD team members assessed the quality of BN structures by measuring the difference between these and normatively correct "gold-standard" structures using "edit distance, " which is the most well-known structural measure in the literature (e.g., Spirtes et al, 2000). However, this approach was facilitated by requiring participants to choose variables out of a set provided, and not requiring probabilities to be entered in the models, thus avoiding both sources of variation in participant answers.…”
Section: Quality Of Reports Causal Models and Trainingmentioning
confidence: 99%